Adapting the Systems Model of Performance Management to major changes in the external and internal organisational environments - H. H. Spangenberg; C. C. Theron (South African Journal of Business Management, 2001)
In essence, this article discusses ways to ensure continued relevance of Performance Management in fast-changing environmental and organisational realities. It starts with the rationale for moving from performance appraisal to Performance Management. In view of some persisting problems with regard to Performance Management, a systems approach to help alleviate these problems is discussed. The current status of Performance Management is reviewed, based on international surveys and a recent report on the way Performance Management best-practice organisations utilise the system. In view of this information, the Systems Model of Performance Management is adapted. The paper is concluded with a discussion and recommendations for future research.
Keywords: 650